2014
DOI: 10.1016/j.freeradbiomed.2014.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Endosomal H2O2 production leads to localized cysteine sulfenic acid formation on proteins during lysophosphatidic acid-mediated cell signaling

Abstract: Lysophosphatidic acid (LPA) is a growth factor for many cells including prostate and ovarian cancer-derived cell lines. LPA stimulates H2O2 production which is required for growth. However, there are significant gaps in our understanding of the spatial and temporal regulation of H2O2-dependent signaling and the way in which signals are transmitted following receptor activation. Herein, we describe the use of two reagents, DCP-Bio1 and DCP-Rho1, to evaluate the localization of active protein oxidation after LPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 59 publications
1
40
0
Order By: Relevance
“…An elegant study of epidermal growth factor (EGF) stimulation of ER-localized Nox4 showed that the native ER-localized PTP1B became oxidatively inactivated and that the ER targeting of PTB1B was required for its inhibition and for effective EGF-stimulated proliferation [81]. Also, recent imaging of H 2 O 2 generation [83, 84] and protein oxidation [85, 86] show that localized buildup of H 2 O 2 occurs proximally to growth factor receptors and oxidatively-modified targets. In endosome-mediated growth factor and cytokine signaling, the H 2 O 2 generation localized proximal to these so-called “redoxosomes” is required for effective downstream signaling [74, 85].…”
Section: Localization Of H2o2-mediated Signaling Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…An elegant study of epidermal growth factor (EGF) stimulation of ER-localized Nox4 showed that the native ER-localized PTP1B became oxidatively inactivated and that the ER targeting of PTB1B was required for its inhibition and for effective EGF-stimulated proliferation [81]. Also, recent imaging of H 2 O 2 generation [83, 84] and protein oxidation [85, 86] show that localized buildup of H 2 O 2 occurs proximally to growth factor receptors and oxidatively-modified targets. In endosome-mediated growth factor and cytokine signaling, the H 2 O 2 generation localized proximal to these so-called “redoxosomes” is required for effective downstream signaling [74, 85].…”
Section: Localization Of H2o2-mediated Signaling Processesmentioning
confidence: 99%
“…Also, recent imaging of H 2 O 2 generation [83, 84] and protein oxidation [85, 86] show that localized buildup of H 2 O 2 occurs proximally to growth factor receptors and oxidatively-modified targets. In endosome-mediated growth factor and cytokine signaling, the H 2 O 2 generation localized proximal to these so-called “redoxosomes” is required for effective downstream signaling [74, 85]. Thus, models for Prx involvement in regulating H 2 O 2 -mediated cell signaling processes must be compatible with the necessity for H 2 O 2 to act locally during signal transduction.…”
Section: Localization Of H2o2-mediated Signaling Processesmentioning
confidence: 99%
“…S3) during responses to LPA, a lipid growth factor produced by prostate cancers and found in the ascites fluid of many ovarian cancers [53, 54]. Our group has previously shown that LPA induces the intracellular formation of H 2 O 2 in these cell lines and that the H 2 O 2 is necessary for the proliferative response of these cell lines to LPA [9, 10]. In serum-starved SK-OV-3 cells, there is no detectable pattern for changes in sulfenic acid formation in the total population of ERK1/2 in response to LPA; instead, it appears that total ERK1/2 is continuously oxidized across the time course (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An important milestone in support of ROS as regulators of cell signaling was the discovery in the mid-1990s by Sundaresan et al that H 2 O 2 generation was required to elicit appropriate proliferative responses to Platelet-Derived Growth Factor (PDGF) in primary rat vascular smooth muscle cells [5]. Roles for H 2 O 2 as a signaling mediator have now been demonstrated in many cell types and in vivo models [68], including our recent work establishing the important role of H 2 O 2 in the proliferative responses to lysophosphatidic acid (LPA), a bioactive lipid synthesized by ovarian and prostate cancer cells and cell lines [9, 10]. ROS have also been implicated in diverse signaling processes such as migration by endothelial cells [11], stem cell pluripotency and differentiation [12], and chondrocyte response to fibronectin fragments [13].…”
mentioning
confidence: 99%
See 1 more Smart Citation